Two-nucleon transfer in the 58Ni(p;3He)56Co reaction at incident energies of 80, 100 and 120 MeV - Van Zyl, Johannes Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.